THE SUGAR INDUSTRY - FRISBIE ILLESCAS, RAFAEL (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1940)
Review, with 28 references ABSTRACT AUTHORS: W C Tobie
CIENC MEX
Keywords: SUGAR INDUSTRY; MULTIDISCIPLINARIA; INGENIERIA Y TECNOLOGIA QUIMICA; QUIMICA INDUSTRIAL